Misères du présent, richesse du possible - Sarfati, Hedva (Relations industrielles / Industrial Relations, 1998)
The article reviews the book, "Misères du présent, richesse du possible," by André Gorz.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; work